Design and development of a biomimetic solar tree for sustainable cogeneration : An energy and exergy assessment - Kumaresen, Mohanaravi; Mahendran, Samykano; Satesh, Namasivayam; K., Kadirgama; Noor, M. M.; Subbarama, Kousik Suraparaju (EDP Sciences, 2024)
Solar energy is becoming an increasingly popular and important source of renewable energy. Solar trees have emerged as a novel and innovative approach to harvesting solar energy. Solar trees are artificial structures that mimic the shape and function of trees, with branches or leaves that contain photovoltaic cells to convert sunlight into electricity. The solar tree generates both electrical and thermal energy from solar radiation. The present study tested the thermal (module temperature, heat loss coefficient), electrical (power output), and operating parameters of a solar tree at Universiti Malaysia Pahang, Pekan, Malaysia, on a typical sunny day. First-law analysis and second-law analysis were carried out to determine exergy losses during the photovoltaic conversion process of solar trees. The data obtained from the experiment is utilized to determine the energy and exergy efficiencies of the solar tree. The energy efficiency ranges from 16.8% to 8.3% throughout the day, displaying some variability. However, as for the exergy efficiency of the photovoltaic solar tree under consideration, it is observed to be lower, ranging from 16.1% to 6.6% for electricity generation. It is observed that the exergy losses increased with increasing module temperature and a drop in exergy efficiency.